World Regional Geography People, Places and Globalization (Open textbook library., 2016)
World Regional Geography: People, Places and Globalization is designed for students to experience and study as much of the world as possible within a limited amount of time. It gives students the fundamental concepts and the latest data regarding world places in a concise, easy-to-read format. This World Regional Geography textbook focuses on the primary issues that have created our cultural and societal structures, and presents them within a framework for global understanding. A pattern of development is outlined from the imprint that European colonialism had on culture to the impact that giant retail corporations like Wal-Mart have on consumerism. Within this framework, the textbook takes a regional approach to globalization and world geography, as each chapter focuses on one subject or region. The first unit covers the basic concepts of location, the environment, and global economic dynamics. Then, these basic concepts, theories, and principles are presented for each region on a chapter-by-chapter basis. The basic concepts are covered using real world examples to provide purpose and relevance for the students. And each lesson begins with learning objectives and ends with key takeaways to stimulate critical thinking about each topic or region. Basic spatial concepts are also tracked throughout the text to connect ideas and apply concepts to every region of the world. Special sections on relevant topics are also distributed throughout the book. With each chapter focused on one region, the textbook provides professors with some course management and flexibility. The text is also brief enough to provide additional flexibility if professors want to include specialized information from outside sources. World Regional Geography: People, Places and Globalization provides students with a working knowledge of world geography in an easy-to-read format. Basic geographic concepts of world places are presented in concise chapters, and each chapter provides a foundational framework for understanding the development patterns of world regions. See for yourself and take a look at the book today!